Faktor Resiko Preeklampsia Berat Di Ruang Bersalin Rumah Sakit Umum Daerah Dr. Moh. Soewandhi Surabaya - Latifiyan Nurnaningtiyas Aminoto; Setyawati Soeharto Karyono; Dina Dewi S. L. I. (coba, 2013)
Severe preeclampsia is a problem that causes emergency, thus increasing morbidity and maternal mortality. There are several risk factors that influence the occurrence of severe preeclampsia. This study aimed to explore the risk factors associated with severe preeclampsia. The study design is cross sectional. sample 64 respondents, divided into 32 severe preeclampsia and mild preeclampsia 32 hospitals in the delivery room. dr. Moh. Soewandhi Surabaya. Logistic regression analysis of the test, it was found that obesity and stress is a risk factor that significantly affects the occurrence of severe preeclampsia.